Notice of a Silver Cup; formerly belonging to the family of Calder of Assuanley, in Strathbogie (Proceedings of the Society of Antiquaries of Scotland, 1858)
The article begins with various legends about the theft of the Cup of Finhaven, another silver cup that the subject of this article has often been mistaken for. The author then moves on to the accurate history of the article's subject and presents the documentary evidence to support this history.